2001
DOI: 10.1007/bf02897304
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle, stress and cortisol response: Review II

Abstract: To prevent lifestyle related diseases, it is important to modify lifestyle behavior. The control of mental stress level and prevention of mental stress-related diseases have become one of the most important problems in Japan. To check mental stress level objectively during the early stage of stress-related diseases and determine appropriate coping methods, it is necessary to design a useful index for mental stress. Cortisol is a steroid hormone secreted by the adrenal cortex. This is an essential hormone to hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 95 publications
(130 reference statements)
0
13
0
Order By: Relevance
“…Both the decrease in body weight gain and the suppression of DNA damage may be due to the additive action and/or synergistic effects of the antioxidants including dietary fiber, vitamins, lycopene, anthocyanin, polyphenol, potassium, isoflavone, acetic acid, amino acid(s), and lactic acid bacteria, and so on [2,17,18]. It has been shown that mental and physiological stresses induce excess reactive oxygen species (ROS) and worsen lifestyle-related diseases [3,5,6]. The presence of excess ROS can cause cellular damage via oxidation of biomolecules, including DNA, proteins and polyunsaturated fatty acids, causing a variety of diseases such as cancer, Parkinson's disease, and cardiovascular disease [1,2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the decrease in body weight gain and the suppression of DNA damage may be due to the additive action and/or synergistic effects of the antioxidants including dietary fiber, vitamins, lycopene, anthocyanin, polyphenol, potassium, isoflavone, acetic acid, amino acid(s), and lactic acid bacteria, and so on [2,17,18]. It has been shown that mental and physiological stresses induce excess reactive oxygen species (ROS) and worsen lifestyle-related diseases [3,5,6]. The presence of excess ROS can cause cellular damage via oxidation of biomolecules, including DNA, proteins and polyunsaturated fatty acids, causing a variety of diseases such as cancer, Parkinson's disease, and cardiovascular disease [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that mental and physiological stresses induce excess reactive oxygen species (ROS), worsen lifestyle-related diseases, cause cellular damage via oxidation of biomolecules, including DNA, proteins and polyunsaturated fatty acids, and finally induce a variety of diseases such as cancer, Parkinson's disease, and cardiovascular diseases [1][2][3][4]. In addition, unhealthy lifestyles such as excessive intake of high-fat diet and lack of exercise are prevalent among people today, and they can induce, promote and increase the lifestyle-related diseases [5][6][7][8][9]. The authors have been studying biological antioxidant defense systems induced by a variety of stresses and the antioxidant effects against reactive oxygen species [10][11][12][13][14][15], and are currently interested in the contribution of biological antioxidant defense system and food to the relationship between obesity and stress, investigating the possibility of utilizing beneficial effects of mild stress [7,16].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies pinpointed salivary cortisol as the hormone index responsible for the activity of the neuroendo- crine axis when it is sped up from several stressor performances or physical efforts [6] [7].…”
Section: Discussionmentioning
confidence: 99%
“…The haematological parameters in winter swimmers show strong non pathological modifications [5]. Moreover, other hormones can be found in saliva for assessing stress beyond cortisol [6] [7]. As compared to plasma analysis, easy and not-invasive saliva collection represents a significant advantage to every research that necessarily involves very large number of samples [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…Exercise and rest have been reported to affect disease development and recovery 35 , 36 , 37 ) , and alcohol consumption and physical activity were the most important lifestyle predictors of sleep disorders 38 ) . Smokers are less likely to exercise, and people who like to perform exercise tend to eat more fresh food 39 ) .…”
Section: Introductionmentioning
confidence: 99%